Weather, psychological wellbeing and mobility during the first wave of the Covid-19 pandemic - Ashley Burdett; Apostolos Davillas; Ben Etheridge (Global Labor Organization (GLO), 2021)
To reduce infection rates during the first UK wave of the COVID-19 outbreak, a first lockdown was announced on March 23, 2020, with a final easing of the restrictions on July 4, 2020. Among the most important public health costs of lockdown restrictions are the potential adverse effects on mental health and physical activity. Using data from the UK Household Longitudinal Study (UKHLS) and Google COVID-19 Mobility Reports we find evidence of reduced park mobility during the initial period of the first UK lockdown and confirm existing evidence of worsening psychological wellbeing. Linkage with weather data shows that contrary to popular belief, weather conditions do not exacerbate the mental health consequences of the pandemic, while we find systematic links between park mobility and weather over the same period. Our results highlight the importance of promoting the existing guidelines on regular exercise during winter lockdowns.
Keywords: I10; I12; C23; 330; COVID-19; mental health; mobility; weather conditions